HUBUNGAN PENGETAHUAN, SIKAP IBU DAN DUKUNGAN KELUARGA MENGENAI KUNJUNGAN IMUNISASI PADA MASA PANDEMI COVID-19 DI PMB BIDAN L KABUPATEN CIANJUR - Damayanti, Destiana; Indriati, Maya; Rahmawati, Naili (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Immunization is a way that is done to cause or increase the immunity of the individual to the disease. Since Indonesia reported the first case of coronavirus 19 (Covid-19) in March 2020, routine immunization coverage to prevent childhood diseases has decreased. This study aims to find out how the relationship of knowledge, maternal attitudes and family support regarding immunization visits during the covid-19 pandemic. The population of 100 mothers who have children 0-24 months and the sample of 80 people is determined by the slovin formula. Sampling techniques used are accidental sampling. Research instruments using questionnaires containing questions and statements. The data was analyzed using the Chi-Square test. The mother's knowledge of immunization visits is good which is as many as 67 people (83.8%), and there is no relationship between knowledge of immunization visits (p-value = 0.313). The attitude of mothers about immunization visits is positive and negative as many as 40 people (50%), and there is no relationship between the mother's attitude towards immunization visits (p-value = 0.496). Family support on immunization visits is supporting as many as 42 people (52.5%), and there is a link between family support to immunization visits (p-value = 0.000). So it can be concluded that the knowledge, attitude of the mother and family support in immunization visits during the covid-19 pandemic should be improved because immunization can lower the death rate of toddlers.